The naked Neanderthal : a new understanding of the human creature - Slimak, Ludovic, 1973- (Pegasus Books, 2024)
"For over a century we saw Neanderthals as inferior to Homo Sapiens. More recently, the pendulum swung the other way and they are generally seen as our relatives: not quite human, but similar enough, and still not equal. Now, thanks to an ongoing revolution in paleoanthropology in which he has played a key part, Ludovic Slimak shows us that they are something altogether different--and they should be understood on their own terms rather than by comparing them to ourselves. As he reveals in this stunning book, the Neanderthals had their own history, their own rituals, their own customs. Their own intelligence, very different from ours." --